2013
DOI: 10.1007/978-81-322-1656-8_35
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of the Tribological Properties of CuO Nano-Lubricants at Elevated Temperatures

Abstract: Tribofilms formed from Copper oxide (CuO) nanoparticles in the nano-lubricant under boundary/thin film lubrication conditions have been studied. The tribological performance is linked to the tribofilm properties and consequently to the lubricating conditions. In the present study, analysis of mineral oil (paraffin oil) and vegetable oils (coconut oil and mustard oil) as a nano-lubricant has been carried out in the perspective of its tribological behaviour using a pin-on-disc tribometer. Small quantities of CuO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The formation of tribo-films, exfoliation of nanoparticles and filling of asperities with nanoparticles were concluded as the reasons for this particular phenomenon. Thottackkad et al [40] and Koshy et al [41,42] investigated the effect of CuO nanoparticle additives in coconut oil and observed that the lubricant properties of the coconut oil were enhanced by the addition of CuO nanoparticles at an optimum concentration of 0.34 wt.%. Further, the surface roughness value was considerably reduced by the utilization of these nanolubricants.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of tribo-films, exfoliation of nanoparticles and filling of asperities with nanoparticles were concluded as the reasons for this particular phenomenon. Thottackkad et al [40] and Koshy et al [41,42] investigated the effect of CuO nanoparticle additives in coconut oil and observed that the lubricant properties of the coconut oil were enhanced by the addition of CuO nanoparticles at an optimum concentration of 0.34 wt.%. Further, the surface roughness value was considerably reduced by the utilization of these nanolubricants.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many researches are being carried out in the field of nanolubrication to explore the possibilities in development of sustainable, ecofriendly and bio-degradable lubricants. Many investigators have identified that the addition of nanoparticles can magnify the required properties of lubricating oils, if properly mixed in definite ratios [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%